READING COMPREHENSION WITH METACOGNITIVE STRATEGY (Universitas Pamulang, 2021)
Two factors contribute to students' lack of passion and participation in reading classes. For starters, pupils' reading skills are lacking due to a lack of imagination, participation, and discipline. Second, instructors' tactics are less diverse and participatory. As a result, students are quickly bored and fearful of reading. To address these concerns, the researcher used action research in the classroom to design a metacognitive technique that included three key strategies: planning, monitoring, and evaluation. According to research, employing metacognitive tactics can encourage pupils to read more. This method also boosts pupils' enthusiasm for reading activities. The majority of the pupils was engaged and enjoyed reading, according to the results of the observational analysis of their reactions. Based on the survey has results that reveal 80.55 percent of pupils fell happy do the reading and 75.94 percent of students participate in it. Finally, metacognitive technique can boost student interest and reading engagement in SMA Negeri 1 Panyabungan English books for 10th graders. It is intended that the findings of the study will be useful to other academics and teachers who are involved in conducting research and teaching initiatives, particularly in the field of reading.